Portfolio Assessment to Measuring Capabilities Communications and Collaborations of Grade V Students in Elementary School - Rizal, M. Khairu; Yulianti, Dwi; Handoko; Rosidin, Udang (Universitas Pendidikan Ganesha, 2023)
One form of assessment that can assess students' abilities as a whole, process and results, is portfolio assessment. The problem in this study originates from the results of a needs analysis on student learning assessments. This study aims to produce a feasible and effective portfolio assessment to measure the communication and collaboration skills of fifth grade elementary school students. This research is a Research and Development (R&D) type of research, the development was carried out referring to the theory of Borg & Gall. The data collection tool uses a valid and reliable portfolio assessment. The data analysis technique uses a paired t test with a calculated result of 0.000 or less than 0.05, which means that there is a difference between the pretest and post-test results for students. Based on this research, it can be concluded that portfolio assessment is effective in improving students' communication and collaboration skills. Based on the conclusions above, suggestions from researchers regarding students' communication and collaboration skills can be improved by students practicing questions as often as possible and being serious about following the learning process according to the assessment aspects.